Treatment with Repository Corticotropin Injection in Patients with Rheumatoid Arthritis, Systemic Lupus Erythematosus, and Dermatomyositis/Polymyositis - Ho-Mahler N (Dove Medical Press, 2020)
Nancy Ho-Mahler,1 Beni Turner,2 Michael Eaddy,2 Mark L Hanke,1 Winnie W Nelson1 1Mallinckrodt Pharmaceuticals, Bedminster, NJ, USA; 2Xcenda, Palm Harbor, FL, USACorrespondence: Nancy Ho-MahlerMallinckrodt Pharmaceuticals, 1425 U.S. Route 206, Bedminster, NJ 07921, USATel +1 747 239 0007Fax +1 314 654 9440Email Nancy.Mahler@mnk.comPurpose: Repository corticotropin injection (RCI) is indicated for a number of autoimmune-mediated diseases including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and dermatomyositis (DM)/polymyositis (PM). To better understand the practice patterns and outcomes of RCI in patients with RA, SLE, or DM/PM, we conducted a retrospective medical record analysis.Patients and Methods: Participating providers selected deidentified medical records of patients meeting the inclusion criteria (age ≥ 18 years; physician-reported diagnosis of RA, SLE, or DM/PM; initiation of treatment with RCI between 1/1/2011 and 2/15/2016; ≥ 3 in-office visits with same site/provider). Collected data spanned 12 months before and after the first prescription date for RCI. Analyses included patient demographics and clinical history, RCI treatment patterns, and physician’s impression of change.Results: Data from 54 patients with RA, 30 patients with SLE, and 8 patients with DM/PM were analyzed. The most frequently reported reasons for initiating RCI were lack of efficacy with prior treatment, acute exacerbation of disease, and use as add-on to ongoing therapy. The most common initial RCI dosing, 80 U twice weekly, was used for 84% of patients with RA, 75% with SLE, and 86% with DM/PM. The mean duration of treatment was 4.8, 6.5, and 6.8 months for RA, SLE, and DM/PM, respectively. Among the 57 patients with data on physician’s impression of change with RCI, 78.1% of patients with RA, 94.7% with SLE, and 66.7% with DM/PM had a rating of “improved,” and the mean time to best impression of change was 3.4, 4.3, and 3.4 months for RA, SLE, and DM/PM, respectively.Conclusion: This study reports the real-world patient profile, use patterns, and outcomes of patients who used RCI for the treatment of RA, SLE, and DM/PM. These data can inform appropriate use and clinical expectations when using RCI.Keywords: adrenocorticotropic hormone, analogue, ACTH, immunomodulatory, real-world patients